A CIDADANIA NA GESTÃO DOS ATOS PÚBLICOS PELA PARTICIPAÇÃO NO PLANO DIRETOR (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The present work directs in the investigation of the importance of citizenship in the realization of the collective rights listed in the norms of the master plans, behold, complying with the final norm of the Master Plan is a way of composing and guaranteeing the realization of citizenship. The right to the city is linked to the notion of equality, access, justice, security, factors that, if obstructed, result in a negative not only of the individual interests of citizens, but, above all, of the collective interests of the population. The Master Plan is the urban planning instrument recognized as the maximum instrument of municipal public management. However, its implementation is usually not fully implemented, causing great frustration to citizens. Still, it is observed that the review of these plans, so that the new needs of the population are met, has not been carried out within the stipulated period. They are, therefore, causes that harm collective rights and go against the legal and democratic order of citizenship and need to be fought. Such factors would generate administrative improbity to the municipal public agent, but, due to the new wording given to the Improbity Law and interpretations, this penalty would no longer be applicable for such reasons. Thus, the research, which took place through a bibliographic review, concluded that only through the exercise of citizenship will citizens be able to see the fundamentals of the Master Plan norm implemented and, consequently, the substantiated needs for them materialized.